2007. Multidirectional Transmission of Clostridioides difficile in Families with Young Infants. (15th December 2022) - Clayton, Jason; Golonka, Gregory; Maruskin, Lynn; Jencson, Annette; Hailes, Jennifer; Cadnum, Jennifer; Donskey, Curtis; Toltzis, Philip
Abstract: Background: Infants frequently excrete toxigenic C. difficile asymptomatically during their first year of life. Prior studies have demonstrated an association between acquisition of community acquired C. difficile infection in adults and contact with an infant, suggesting the latter is a reservoir of the organism. To probe this possibility further, we aimed to examine how frequently C. difficile is transmitted from infants to otherwise healthy adult caregivers. Methods: Families presenting to a suburban pediatric clinic for their infants' 4-month well-child visit were recruited. Consenting parents were instructed to mail soiled diapers every 2 weeks to a research laboratory with experience cultivating C. difficile, until their baby was 8 months old. Parents were requested to concomitantly send soiled toilet paper, or a rectal swab via a moistened wipe, from themselves. Samples were cultured for C. difficile by direct plating on selective media plus using a more sensitive broth enrichment method. For family groups with C. difficile colonization, PCR ribotyping was used to determine the relatedness of selected baby and parent isolates. Results: To date 17 families have submitted at least 1 set of samples. Follow up has ranged from 2 to 16 weeks (median 8). In 15/17 families, at least 1 sample was positive for C. difficile : in 4/15 only a parent was positive, in 3/15 the baby plus 1 parent were positive, and in 8/15 all family members were positive. There were no families in which only the baby yielded the organism. The index was the mother in 6/15 families, and the baby in 3/15 families; in 6/15 families, the baby plus >/= 1 parent were initially positive simultaneously. Excretion tended to be prolonged in infants (up to 16 weeks) whereas positivity was more transient in the adults. Isolates from 10 families in which the baby and at least 1 adult were positive for C. difficile were subjected to ribotyping; in 8/10 families the baby's ribotype was concordant with >/= 1 adults'. Conclusion: C. difficile colonization is common among healthy household members caring for an infant. Longitudinal observation suggests that transmission is multidirectional, with the organism passed from adult to baby and from baby to adult. Disclosures: All Authors : No reported disclosures.